At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

passes through (-1, -5) and (2, 6)

Sagot :

Answer:

[tex]y = \frac{11}{3}x + -\frac{4}{3}[/tex]

Step-by-step explanation:

[tex]y = mx + b\\m = \frac{-5 - 6}{-1 - 2} = \frac{-11}{-3} = \frac{11}{3} \\\\y = \frac{11}{3}x + b\\6 = \frac{11}{3}(2) + b\\6 = \frac{22}{3} + b \\6 - \frac{22}{3} = b \\b = -\frac{4}{3}\\\\y = \frac{11}{3}x + -\frac{4}{3}[/tex]